Bird's‐eye view of analog and mixed‐signal chips for the 21st century. (8th February 2021) - Martins, Rui P.; Mak, Pui‐In; Chan, Chi‐Hang; Yin, Jun; Zhu, Yan; Chen, Yong; Lu, Yan; Law, Man‐Kay; Sin, Sai‐Weng
SUMMARY: The Internet of Everything (IoE), clearly a 21st century's technology, brilliantly plays with digital data obtained from analog sources, bringing together two different realities, the analog (physical/real), and the digital (cyber/virtual) worlds. Then, with the boundaries of IoE still analog in nature, the required functions at the interface involve sensing, measuring, filtering, converting, processing, and connecting, which imply that the analog layer governs the entire system in terms of accuracy and precision. Furthermore, such interface integrates several analog and mixed‐signal subsystems that comprise mainly signal transmission and reception, frequency generation, energy harvesting, data, and power conversion. This paper sets forth a state‐of‐the‐art design perspective of some of the most critical building blocks used in the analog/digital interface, covering wireless cellular transceivers, millimeter‐wave frequency generators, energy harvesting interfaces, plus, data and power converters, that exhibit high quality performance achieved through low‐power consumption, high energy‐efficiency, and high speed. Abstract :